2013
DOI: 10.1159/000350306
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cancer-Associated Anaemia: Results from a Two-Day Cross-Sectional Survey in Germany

Abstract: Background: The aim was to re-evaluate the current prevalence and management of cancer-associated anaemia as defined by the World Health Organisation (WHO) and related risk factors. Patients and Methods: This was a prospective, 2-day web-based cross-sectional survey in cancer patients with non-myeloid malignancies in German outpatient clinics. Results: 89 centres collected data from 3,867 patients, of whom 74% received active cancer therapy. The median age was 65 years (range 19-99 years) and almost two-thirds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
2
12
1
2
Order By: Relevance
“…Findings strikingly similar to this study’s were reported in a retrospective observational study in France ( N  = 276) and a recent cross-sectional survey in Germany ( N  = 3,867) [42, 43]. Both studies showed frequent use of RBC transfusions in anaemic cancer patients and disregard of available treatment options for iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Findings strikingly similar to this study’s were reported in a retrospective observational study in France ( N  = 276) and a recent cross-sectional survey in Germany ( N  = 3,867) [42, 43]. Both studies showed frequent use of RBC transfusions in anaemic cancer patients and disregard of available treatment options for iron deficiency.…”
Section: Discussionsupporting
confidence: 90%
“…The present data are however very different from those collected in France in 2006 and published by Guardiola et al [24]. Their analysis reported that 17 % of anemic patients were not treated for anemia, while a German analysis from a Web-based prospective survey conducted in 2009-2010 [25] showed that two thirds of patients with Hb ≤12 g/dL were not treated for anemia.…”
Section: Discussioncontrasting
confidence: 98%
“…Nevertheless, the most recent large-scale studies still maintain that anemia and iron deficiency are underdiagnosed [21,22] and often inadequately treated [14,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia is a common problem in patients with cancer [3, 4, 35]. Although it has a negative impact on prognosis and treatment results, anemia is undertreated and is not a major concern among oncologists [4, 35].…”
Section: Discussionmentioning
confidence: 99%